2012
DOI: 10.1074/jbc.m111.279331
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Calcineurin B-like (CBL) Calcium Sensor Proteins by Their CBL-interacting Protein Kinases (CIPKs) Is Required for Full Activity of CBL-CIPK Complexes toward Their Target Proteins

Abstract: Calcineurin B-like proteins (CBLs) represent a family of calcium sensor proteins that interact with a group of serine/threonine kinases designated as CBL-interacting protein kinases (CIPKs). CBL-CIPK complexes are crucially involved in relaying plant responses to many environmental signals and in regulating ion fluxes. However, the biochemical characterization of CBL-CIPK complexes has so far been hampered by low activities of recombinant CIPKs. Here, we report on an efficient wheat germ extract-based in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
139
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 69 publications
6
139
1
Order By: Relevance
“…Our results showed that although the phosphomimicking mutation T168D greatly enhanced the kinase activity of CIPK24/ SOS2ΔC, the corresponding T190D mutation produced little effect on CIPK23ΔC. These data correlate well with those obtained with full-length proteins expressed by using a wheat germ extract-based in vitro transcription/translation protocol (13). In these experiments, the catalytic efficiency (k cat /K m ) was roughly eightfold lower for CIPK23 than for CIPK24/SOS2.…”
Section: Cipk23 and Cipk24/sos2 Adopt A Conserved Inactive Conformationsupporting
confidence: 77%
See 3 more Smart Citations
“…Our results showed that although the phosphomimicking mutation T168D greatly enhanced the kinase activity of CIPK24/ SOS2ΔC, the corresponding T190D mutation produced little effect on CIPK23ΔC. These data correlate well with those obtained with full-length proteins expressed by using a wheat germ extract-based in vitro transcription/translation protocol (13). In these experiments, the catalytic efficiency (k cat /K m ) was roughly eightfold lower for CIPK23 than for CIPK24/SOS2.…”
Section: Cipk23 and Cipk24/sos2 Adopt A Conserved Inactive Conformationsupporting
confidence: 77%
“…The required phosphorylation of the C-terminal region of CBLs by CIPKs to achieve fully functional activation of the CBL-CIPKs complexes may be central to understand why the moderate NAF motif-mediated stimulation of the in vitro CIPK23 (Fig. 2) is absolutely required for in vivo activation of AKT1 K + channel (13). This data additionally supports the idea that CBL phosphorylation may affect the structure of the CBL-CIPKs complexes and consequently, their activity.…”
Section: Cipk23 and Cipk24/sos2 Adopt A Conserved Inactive Conformationsupporting
confidence: 72%
See 2 more Smart Citations
“…CBL1 binding recruits CIPK23 to the plasma membrane and enables autophosphorylation of the kinase . Autophosphorylation and CBL1 binding lead to complete activity of the kinase (Hashimoto et al, 2012). The phosphorylation of AKT1 is essential for its activation at low external potassium concentrations.…”
Section: Introductionmentioning
confidence: 99%